Implementation of the Clean and Green Sidoarjo Program using the Quadruple Helix Concept Approach - Erna Sulistiawati; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to analyze and describe the implementation of the clean and green Sidoarjo program using the quadruple helix approach in Kenongo Village, Tulangan District, Sidoarjo Regency. This research is a descriptive qualitative research using purposive sampling informant determination technique. Techniques for collecting data are interviews, observations, documentation and literature studies. The data analysis technique uses Miles and Huberman which consists of four components, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that with this program, people understand that waste also has economic value and they create activities related to the program. People are indifferent to the programs and socialization provided by the government. In addition, poor communication and coordination with stakeholders such as RT in the village. And there are several obstacles in implementing the program, namely the corona virus and many residents who are urbanizing.